Pengaruh Kinerja Keuangan Daerah Terhadap Alokasi Belanja Modal Provinsi Sumatera Utara - M. Irvan Fahrul Sitorus; Isnaini Harahap; Rahmat Daim Harahap (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research aims to analyze the influence of regional financial performance on capital expenditure allocation. The data used is secondary data from 2018 to 2021 which comes from regional financial reports. Data analysis was carried out using multiple linear regression. The research results show that regional financial performance has a positive and significant effect on capital expenditure allocation. This shows that the better the regional financial performance, the greater the capital expenditure allocation that can be allocated. The ability of regional governments to manage their regional finances can be measured by analyzing regional financial performance. Regional financial performance consists of financial ratios. These financial ratios are used to assess regional financial independence in financing the implementation of regional autonomy, measure effectiveness and efficiency in realizing regional income, measure the extent of regional government activity in spending its regional income, measure the contribution of each source of income in the formation of regional income, see growth/development of income and expenditure during a certain period of time.